A lavratura do termo circunstanciado de ocorrência pela polícia militar do Amazonas. - Morillas, Juan Pablo Moraes (2018)
Using the hypothesis that the PMAM has a legal attribution to perform the TCO drawing, that it is possible to implement, improve and improve the TCO drawdown by the PMAM, and that the implantation and drawing of the TCO by the PMAM is a step the modernization, optimization, integration and efficiency of the Public Security System in the State of Amazonas, the work seeks, through this association between the crisis of the model of "police socks", Full Cycle of Police and drafting of the TCO by the Military Police to make a study and analysis that help in the planning and development of actions that allow the PMAM to contribute to the integration, modernization, optimization, and improvement of the efficiency of the Public Security system of the State of Amazonas. In the research it was shown that the PMAM can legally cultivate the TCO. The level of knowledge, acceptability and opinions (technical and personal) of the officers and squares of the military police of Amazonas, Santa Catarina and Rio Grande do Sul were also raised on the drafting of the TCO. It was also verified the degree of acceptability, and the technical and personal opinions of the Magistrates, Promoters of Justice, Delegates, Investigators, Secretaries of State and other professionals in the Public Security area, on the preparation of the TCO to be carried out by the PMAM. It was evaluated whether the implantation and accomplishment of the TAC preparation by PMAM is feasible and feasible. In addition, it was identified the favorable and unfavorable indicators for the modernization, optimization, integration and efficiency, which may arise from the implementation and realization of the TCO drawdown by PMAM, as well as the analytical results. In the end, according to what was raised, it was apparently demonstrated that it is perfectly feasible to carry out TAC readings by PMAM, stressing that there is a need for measures to be implemented. A proposal for an implementation plan was also drawn up for the preparation of the TCO by the PMAM, which is an annex to this dissertation (APPENDIX C), a proposal for a regulatory Decree on the part of the Chief Executive of the State Executive Branch. Decree in ANNEX A), as well as a proposal for a decision to be issued by the Court of Justice of Amazonas, in order to resolve any discomfort between the state police institutions. It is worth mentioning that the research also allowed us to address other issues related to the implementation of the Police Full Cycle by the PMAM, and other issues that are related to how it happened and how has evolved this process of drafting the TCO and the path of military police institutions towards to the adoption of the Full Cycle of Police. In addition, I must mention the valorization of these professionals and the adoption of a positive legislative agenda by the Government and the State Legislative Branch, together with these institutions, with a view to managing for results. Thus, in view of all the aspects covered and in spite of the controversy of the theme, we can have an idea of the benefits that can be incorporated into the Public Security System of the state of Amazonas, system, if the PMAM performs the TCO in relation to the occurrences that it attends, at the place of the facts, and also to verify that this process means that the PMAM will carry out the complete cycle of police in relation to to criminal offenses of lesser offensive potential, which would seem to be a key step for the PMAM to complete the Full Police Cycle as a whole in the future.